Estratégias para obtenção de duplo – haploides e progênies indutoras de haploidia em milho - Ribeiro, Camila Bastos (2016)
One of the limitations of the double haploid lines development in vivo is to perform a haploid identification with low frequency of false positives and subsequent chromosome duplication. Obtaining haploid inductors with high induction rates is also a very important point that greatly facilitates the use of this technology. The aim of this study was to identify the haploid R-Navajo marker, length and root color, vigor of plants, flow cytometry, chromosome counting and microsatellite markers and also obtain double haploid lines. In addition, we evaluated 14 S0:1 progenies and seven S2:3 progenies of maize in relation to their haploid induction rate. After that we compared the selection of individuals for different strategies involving selection among, between and within and only within progenies and also the effect of indirect selection for plants with purple endosperm instead of the haploid induction. The experiments were conducted in the experimental area of the Biology Department of UFLA in Lavras, Minas Gerais, in the agricultural years 2012/2013 and 2014/2015. An experiment was conducted in each year, and the design used in both was completely randomized, with one and two replications in the 2012/2013 and 2014/2015, respectively. The haploid and purple induction were evaluated in the cross between the progenies and the simple hybrid GNZ9501. We found 552 and 260 haploid in 2012/2013 and 2014/2015, respectively. The haploid identified by flow cytometry, were subjected to a chromosome doubling protocol. It appeared that morphological markers can result in a high proportion of false positives in haploid identification. The use of flow cytometry and DNA codominant molecular markers, are the most recommended for haploid confirmation. It was possible to obtain a double-haploid line with the protocol used. Progenies 2 and 6 proved effective in haploid induction in both years. The selection among and within progenies for haploid and purple induction showed higher genetic gains.